Evaluación de sistemas de manejo de cultivos con base a la agricultura de conservación para adaptación al cambio climático, Granja Experimental Laguacoto III, cantón Guaranda. - Chela Vega, Diana Karolina (2020)
The conventional agriculture model includes large-scale monocultures, with high dependence on external inputs and deficient use of agricultural machinery, and added to climate change, has extremely negative effects on the sustainability of production systems with high negative impacts on natural, social, cultural, economic and environmental capitals. To mitigate these effects, Conservation Agriculture (AC) is a technology that has been making CIMMYT around the world with promising results and indicators that contribute to food security and sovereignty. Bolivar province is the largest producer of soft maize in Ecuador, but is threatened by conventional agriculture, irrational use of agricultural machinery in hillside conditions, severe processes of water and wind erosion, high dependence on inputs intensive monocultures and climate change with the onset of new pests and diseases. This research was carried out at the Laguacoto III Experimental Station, which is at an altitude of 2640 m, a type of clay loam soil and low organic matter soil. The objectives set out in this research were: (i) To evaluate the effect of five technological alternatives for the production of INIAP 103 soft maize, (ii) To measure the effect of eight technological alternatives on the main indicators of the chemistry of soil, (iii) Perform the Partial Budget Economic Analysis (AEPP) and calculate the Marginal Rate of Return (TMR) and (iv) Select promising technological alternatives for adaptation to climate change. Eight treatments were evaluated including conventional and conservation agriculture, crop rotation, use and removal of plant remains. An experimental design of Complete Random Blocks was applied with three repetitions. Variance analysis, Tukey test, complete soil chemistry analysis was performed before and at the end of the two-depth test. At the end of the third year of research, there were clearly significant differences in yields of INIAP 103 variety maize and rotational crops such as line A2 durum wheat, INIAP 480 arbustive beans and cultivar INIAP Tunkahuan quinoa. The content of Organic Matter in Conservation Agriculture treatments increased from a low to medium content and therefore macro and micronutrients. Soil pH is more acidic in the farmer conventional technology. There were no significant effects of soil chemistry indicators between the two depths evaluated. Finally, this research made it possible to select and consolidate valid technological alternatives to improve the sustainability of local maize production systems through the three fundamental principles of AC such as minimal soil removal; conservation of plant remains by at least 50% and crop rotation with wheat, legumes and Andean grains (Lupinus mutabilis and quinoa).